2019
DOI: 10.1039/c9fo01617a
|View full text |Cite
|
Sign up to set email alerts
|

Alginate and HM-pectin in sports-drink give rise to intra-gastric gelation in vivo

Abstract: A polysaccharide drink containing 14% maltodextrin/fructose shows in vivo gelling behaviour as evidenced by magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…CHO hydrogel products have attempted to improve on existing nutrition recommendations (use of CHO with multiple transporters [Jeukendrup, 2010] and gut training [Jeukendrup, 2017]) to target the need for highperformance athletes to achieve high CHO availability during prolonged events conducted at high relative and absolute intensities (Burke et al, 2019). Although there is evidence that these products achieve gelation within the acidic stomach environment as claimed (Marciani et al, 2019;McCubbin et al, 2019), subsequent effects on gastric emptying, intestinal absorption, and delivery to the muscle during exercise remain largely untested. Our review summarized the available literature on the use of these products during prolonged exercise in terms of GI comfort, substrate utilization, and performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHO hydrogel products have attempted to improve on existing nutrition recommendations (use of CHO with multiple transporters [Jeukendrup, 2010] and gut training [Jeukendrup, 2017]) to target the need for highperformance athletes to achieve high CHO availability during prolonged events conducted at high relative and absolute intensities (Burke et al, 2019). Although there is evidence that these products achieve gelation within the acidic stomach environment as claimed (Marciani et al, 2019;McCubbin et al, 2019), subsequent effects on gastric emptying, intestinal absorption, and delivery to the muscle during exercise remain largely untested. Our review summarized the available literature on the use of these products during prolonged exercise in terms of GI comfort, substrate utilization, and performance.…”
Section: Discussionmentioning
confidence: 99%
“…and alginate (a polymer derived from seaweed) undergo gelation on contact with low pH solutions, such as stomach acid, to encapsulate the CHO (Marciani et al, 2019). Enhanced rates of gastric emptying could deliver this "hydrogel" to the small intestine where it dissolves in the higher pH environment for absorption, leading to reduced gut discomfort, enhanced muscle CHO delivery, and performance benefits (Figure 1).…”
mentioning
confidence: 99%
“…A recent review highlighted the lack of evidence for benefits from the use of sodium alginate and pectin added to a CHO beverage on physiological or GID symptoms during moderate intensity exercise ( 36 ). Current, mechanism-driven research has shown that a hydrogel can form around a CHO ( 37 ), which occurs in vivo ( 18 ) and subsequently enhances GE ( 19 ). Following this, however, there have been several studies which showed no differences from “standard” CHO beverages when comparing various physiological markers (e.g., ExCHO, whole-body oxidation rates and blood metabolites) and subjective markers (e.g., RPE and GID symptoms) [as reviewed elsewhere ( 36 )].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first study discussing the potential benefits of adding sodium alginate and pectin to a CHO beverage (17), there has been a growing interest in exploring and quantifying any ergogenic or ergolytic effects (18,(20)(21)(22)(23)(24). Recently, a study by McCubbin et al investigated the effects of sodium alginate and pectin when ingesting 1.5 g .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation